1991
DOI: 10.1002/ppul.1950110312
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FEV1 and transcutaneous oxygen tension in the measurement of airway responsiveness to methacholine

Abstract: The measurement of airway responsiveness in preschool children is hampered by the fact that most tests of airway caliber are difficult to carry out at a young age. Patient cooperation is only needed to a limited extent when transcutaneous oxygen tension (PtcO2) is used as an indicator of airway obstruction following bronchial provocation. In 51 children, aged 6-14 years with asthma we have measured PtcO2 and forced expiratory volume in 1 second (FEV1) concurrently after bronchial provocation, using increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…Previous reports have indicated a relationship between the change in tcPO 2 and respiratory resistance 14 or FEV 1 . 25 Tepper 26 and LeSouëf 23 have measured VЈmaxFRC and oxygen saturation during histamine or methacholine inhalation challenges in infants and demonstrated that significant decreases in both VЈmaxFRC and oxygen saturation were detected after inhalation challenge. Thus, methacholine-induced airway obstruction results in hypoxemia because of narrowing of the airways by smooth muscle constriction and edema in airway mucosa, 27 changes in local ventilation/perfusion ratios, and a subsequent fall in alveolar and arterial P O2 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous reports have indicated a relationship between the change in tcPO 2 and respiratory resistance 14 or FEV 1 . 25 Tepper 26 and LeSouëf 23 have measured VЈmaxFRC and oxygen saturation during histamine or methacholine inhalation challenges in infants and demonstrated that significant decreases in both VЈmaxFRC and oxygen saturation were detected after inhalation challenge. Thus, methacholine-induced airway obstruction results in hypoxemia because of narrowing of the airways by smooth muscle constriction and edema in airway mucosa, 27 changes in local ventilation/perfusion ratios, and a subsequent fall in alveolar and arterial P O2 .…”
Section: Discussionmentioning
confidence: 98%
“…11,15 Recently, van Broekhoven and Wilts reported on the measurement of BHR using the tcPO 2 method; they described its convenience and safety in young children. 12,25 During acute attacks of asthma, it is known that changes in tcPO 2 are linearly related to the severity of the asthma attacks. Previous reports have indicated a relationship between the change in tcPO 2 and respiratory resistance 14 or FEV 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated a relationship between the change in tcPO 2 and Rrs (144) or in FEV 1 (156). Tepper et al and Lesouëf et al demonstrated significant decreases in both V max FVC and oxygen saturation during histamine or methacholine inhalation challenge in infants (158,159).…”
Section: Indirect Measurement Of Lung Function During Provocation Testmentioning
confidence: 96%
“…Wilts et al and Van Broekhoven et al reported the measurement of BHR using the tcPO 2 method in younger children and described its convenience and safety (155,156). During acute attacks of asthma, it is known that the changes in PaO 2 are linearly proportional to the severity of the asthma attacks.…”
Section: Indirect Measurement Of Lung Function During Provocation Testmentioning
confidence: 98%
“…In Europe, the group of academic pediatric pulmonologists continued to expand with, among others, the Danish investigators Hans Bisgaard, working on asthma therapy in children, especially in relation to inhaled corticosteroids (76), and Soren Pedersen and Agertoft and their colleagues working chiefly on the side effects of treatment (77). Johannes de Jongste from the Netherlands was working on measuring airway responsiveness (78) and later on exhaled nitric oxide in children, while Kai-Hakon Carlsen of Norway was undertaking a number of studies, including bronchial provocation in young children and the efficacy of inhaled adrenaline (epinephrine) in bronchiolitis (79). Last but by no means least of this group was Erica von Mutius from Germany, whose studies of the differences in asthma incidence in children between the former East and West Germany started the whole concept of the "dirty environment" hypothesis about the prevention of asthma (80,81).…”
Section: The 1990s-2000؉: Consolidationmentioning
confidence: 99%